Interferensi Bahasa Ibu Terhadap Bahasa Arab di SMA PPM Rahmatul Asri - Ririn Anisa Fitri; Herdah Herdah; Hamsa Hamsa; Saepudin Saepudin; Kaharuddin Kaharuddin (STIQ Amuntai, 2026)
Mother tongue interference remains a challenge in Arabic language learning at SMA PPM Rahmatul Asri, despite the pesantren environment that encourages active use of Arabic. Such interference appears in phonological, morphological, and syntactic aspects in both spoken and written Arabic, as well as in maharah al-qira’ah in the form of mispronunciation, inaccurate vowel length, and inappropriate pauses that affect meaning. This study employed a quantitative correlational design. The population consisted of 150 students, with 60 respondents selected using the Slovin formula and purposive sampling. Data were collected through questionnaires, Arabic grammar tests, and reading performance assessments, and analyzed using descriptive and inferential statistics. The results show that mother tongue interference was predominantly at a moderate level (78.3%), while low and high levels accounted for 11.7% and 10%, respectively. Grammar mastery was also dominated by the moderate category (65%), followed by low (21.7%) and high (13.3%) categories. Meanwhile, maharah al-qira’ah was mostly at a moderate level (48.3%), with 33.3% of students in the high category and 18.3% in the low category. Simple linear regression analysis revealed that mother tongue interference had no significant effect on grammar mastery (Sig. = 0.598 > 0.05) or on maharah al-qira’ah (Sig. = 0.966 > 0.05); therefore, the alternative hypothesis was rejected, and mother tongue interference is understood as a natural linguistic phenomenon in a bilingual context.